Stepping up : how taking responsibility changes everything - Izzo, John B. (John Baptist), 1957- (BK life book., 2012)
Bestselling author John Izzo brings together his distinctive mix of inspiring story-telling and practical advice to tell how we can more effectively bring about positive change by taking responsibility in our work, personal lives, and communities.